Pesquisa-vida-formação e cartografia de afetos no território da Coordenação Pedagógica: diálogos entrecruzados de um diário tese. - Schiavon, Tatiana de Camargo (2024)
In this text, you will find a doctoral thesis anchored in the principles of (auto)biographical approach, as it takes place in/with the itinerancy experienced as Pedagogical Coordinator and researcher in Basic Education. Like this, The objectives proposed here are to understand how the Pedagogical Coordinator gives shape to her experiences and meaning to the profession, in the relationship with what circumscribes the existential territory it inhabits, what are the legal protections, duties, working conditions and training processes that give new meaning to their place in the profession. Path that directed studies and reflections on the field of affections that permeate this entire process of taking of position and construction of a place for oneself in the Pedagogical Coordination. Therefore, a life-training research is assumed, based on the contributions methodological theorists by Sicard Nakayama and Brito (2020), Delory-Momberger (2006), Josso (2002, 2010), Souza (2014), Barbosa (2000), Kastrup (2009) and Freire (1997), in which the method of Cartography of the human and narrative is combined (auto)biographical, in order to follow the processes, learn about the experiences in its creative dimension for the resignification of oneself, both with the group of Pedagogical Coordinators participating in an extension course promoted in favor of research, which was consolidated by uniting the university and the school, as well as an interweaving of the researcher's own experience in life working as Pedagogical Coordinator. This movement of investigation into that research is carried out with others and not about them, led to an analysis interpretative- comprehensive in the light of Souza (2014), giving new meaning to the entire process experienced in itself and in research, a movement that also directed the exercise attentive listening based on Passeggi (2018), recording the entire itinerancy of life intertwined with research in a diary in which listening and writing of oneself and/with the other, opened trails, new routes to understand what circumscribes this professional and academic existential territory lived with the Pedagogical Coordination. The fabrics that were intertwined in the research, in the life and training of all Pedagogical Coordinators involved culminated in the considerations present in this thesis as a movement of transformation and creation of new positions in this territory of Pedagogical Coordination.